Clinical Findings & MR Features in CNS Tuberculosis. A Tertiary Care Hospital Study (Medical Forum Monthly, 2022)
Objective: To know the clinical findings & MR features in CNS Tuberculosis. A tertiary care hospital study.Study Design: cross-sectional studyPlace and Duration of Study: This study was conducted at the Neurology department of Jinnah Postgraduate Medical Centre, Neurology Department DUHS and Medicine Department of Mohtarma Benazir Bhutto Medical College, Karachi from January 2018 to December 2019 for a period of 02 years.Materials and Methods: The research was done on 89 serially registered patients of CNS tuberculosis selectively intracranial pathology in the said institutions. Enrolled subjects were between the age 15 to 52 years suggestive of cerebral tuberculosis with MRI evidence were involved and data was analyzed using the SPSS 25 software.Results: The mean age of subjects was ± SD 31.42 ± 10.84 years while the mean presenting symptoms duration was found 11.46 with SD ± 6.39. Percentage of male patients was 59.6 and Female patients were 40.4 Percent. 37.1% patients have positive family history of tuberculosis. 23.6% subjects have diabetes in their family. The most common presenting symptom was fever 82%, while headache was the second most common features that is 79.8%, neck stiffness was found in 76.4 percent, 68.5% had disturbed conscious level and hemiplegia was seen in 44.9%. Diverse MRI appearances for example enhancement of Basal cistern was found in 20.2 percent, enhancement of meninges in 66.3%, 29.2% have non obstructive hydrocephalus, tuberculomas were found in 67.4 percent patients and last but not the least 25.8 percent subjects have ischemic infarcts. About 14.6 percent patients have mixed MRI appearances a like tuberculomas with meningeal enhancement, basal cistern enhancement with tuberculoma in 9% patients. 12.4 percent patients have cerebral ischemia with tuberculomas. 5.6% patients have typical infarcts with enhanced meninges and ring enhanced tuberculomas.Conclusion: In our study tuberculomas was on the top in MRI findings second most common was meningeal enhancement. Hydrocephalus was on third. So, it is concluded the patients should be referred promptly to tertiary care hospital for better diagnosis of difficult neurological case